Human capital and structural transformation: Quasi-experimental evidence from Indonesia - Karachiwalla, Naureen; Palloni, Giordano (International Food Policy Research Institute, 2019)
This paper provides quasi-experimental evidence on the long-term causal effect of increases in human capital on participation in agriculture. We use variation in male educational attainment generated by Indonesia’s Sekolah Dasar INPRES program, one of the largest ever school building programs. Consistent with the first evaluation [Duflo, 2001], we find that males exposed to a higher program intensity have improved measures of human capital as adults. We then show that treated cohorts are more likely to be employed outside of agriculture–particularly in industry–and less likely to be agricultural workers. Then, exploiting variation in exposure across adjacent districts, we demonstrate that higher INPRES intensity in neighboring districts decreases non-agricultural employment and earnings, consistent with cross-district spillovers mediating the total impacts. Together, the results suggest that government investment in human capital can have profound effects on the rural economy and may help to accelerate shifts away from agriculture.